Contribution to the Grass Flora of Gujarat State - Gandhi, Dhara; Albert, Susy; Pandya, Neeta (Indian Forester, 2017)
The documentation of grasses in the different forest area of Gujarat State was explored. The documentation of grasses in the different forest areas of Gujarat State was explored. Especially in Saurashtra and Central Gujarat, Grass species were collected. Detailed morphological characterization of the vegetative and reproductive parts were carried out using dissecting and binocular microscope (Olympus microscope-SZ2-ILST). Identified species were further confirmed at Blatter Herbaria (St. Xavier’s College, Mumbai).